Female Hypoactive Sexual Desire Disorder: What physicians need to know ? - Ahsan, Mohammad Shamsul (Bangladesh Journal of Medicine, 2024)
Hypoactive sexual desire disorder (HSDD) is a persistent or recurrent deficiency or absence of sexual fantasies and desire for sexual activity that causes marked distress or interpersonal difficulty not related to a medical or psychiatric condition or the use of a substance or medication. Factors responsible are bio-psycho-social and contextual. Earlier female sexuality was not discussed and more so in Bangladesh. Over the past decade there are number of studies in western world and very few in Bangladesh. Survey on female HSDD showed that up to 80% are reluctant to talk about their sexuality to health care providers and at least 50% have discomfort or embarrassment and unwilling to seek treatment. Often vague somatic symptoms are the presenting features. Appropriate knowledge, skills and attitude is crucial to address the issue and comprehensive assessment. Bio-psycho-social factors are related to female HSDD like altered hormones, neurotransmitters and their interactions, medical conditions like diabetis, urinary incontinence and psychiatric illness. The psychological factors, such as boredom, situational stress, self-consciousness about body image, and distraction; and social and contextual factors that include cultural norms, familial teachings, and relationship considerations. Treatment approach also needs to consider the bio-psycho-social aspects. Bangladesh J Medicine, 2024; Vol. 35, No. 2, Supplementation: 145